Design and Construction of a Hydraulic Lift. - Ndahura, Dickens (Kabale University, 2024)
This project is mainly focused on the force acting on the hydraulic lift when it is extended and contracted. Generally, a hydraulic lift is used for lifting and holding heavy-weight components. Material selection plays a key role in designing a machine and also influences several factors such as durability, reliability, strength, and resistance which finally leads to an increase in the life of a hydraulic lift. The design is performed by considering a hydraulic lift as a portable, compact, and suitable for medium type of load application. Drafting and drawing a hydraulic lift system is done using solid works with suitable modeling and imported to any workbench for meshing and analysis. Hence, the analysis of the lift, total deformation load, and equivalent stress was done and all responsible parameters were analyzed to check the compatibility of the design.